2021
DOI: 10.3389/fimmu.2021.616837
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Modulation of T Cells by VEGF-A Counteracted by Anti-Angiogenic Treatment

Abstract: Vascular endothelial growth factor A is known to play a central role in tumor angiogenesis. Several studies showed that VEGF-A is also an immunosuppressive factor. In tumor-bearing hosts, VEGF-A can modulate immune cells (DC, MDSC, TAM) to induce the accumulation of regulatory T-cells while simultaneously inhibiting T-cell functions. Furthermore, VEGFR-2 expression on activated T-cells and FoxP3high regulatory T-cells also allow a direct effect of VEGF-A. Anti-angiogenic agents targeting VEGF-A/VEGFR contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 91 publications
1
72
0
Order By: Relevance
“…Moreover, the recruitment of CD4 + CD25 + Treg cells to CAFs also depends on the chemokine CCL5 according to studies examining breast cancer [ 209 , 210 ]. Other molecules, such as VEGF-A, one of the growth factors released by CAFs, have been observed to directly or indirectly participate in Treg cell induction and maintenance [ 211 , 212 ]. In addition to promoting the recruitment and infiltration of Treg cells, CAFs also promote their transformation to ultimately induce immune suppression.…”
Section: Interaction Between Cafs and The Immune Microenvironment In Tumorsmentioning
confidence: 99%
“…Moreover, the recruitment of CD4 + CD25 + Treg cells to CAFs also depends on the chemokine CCL5 according to studies examining breast cancer [ 209 , 210 ]. Other molecules, such as VEGF-A, one of the growth factors released by CAFs, have been observed to directly or indirectly participate in Treg cell induction and maintenance [ 211 , 212 ]. In addition to promoting the recruitment and infiltration of Treg cells, CAFs also promote their transformation to ultimately induce immune suppression.…”
Section: Interaction Between Cafs and The Immune Microenvironment In Tumorsmentioning
confidence: 99%
“…In addition, some studies have shown that VEGF supports tumor progression by playing a role as an immuno-suppressive factor. 27 VEGF modulates immune cells to induce regulatory T cells' recruitment while simultaneously decreasing the infiltration of cytotoxic T cells (CTLs). 27 Therefore, anti-VEGF agents can increase intratumoral infiltration and the survival of CTLs through vascular normalization and modulation of immune microenvironment, thereby facilitating the response of ICIs to cancer cells.…”
Section: Synergic Effects Of Anti-vegf and Anti-pd-1/pd-l1 Monoclonal Antibodiesmentioning
confidence: 99%
“…27 VEGF modulates immune cells to induce regulatory T cells' recruitment while simultaneously decreasing the infiltration of cytotoxic T cells (CTLs). 27 Therefore, anti-VEGF agents can increase intratumoral infiltration and the survival of CTLs through vascular normalization and modulation of immune microenvironment, thereby facilitating the response of ICIs to cancer cells. In addition, interferon-Îł, which is secreted by Th1 cells and activated by anti-PD-1/PD-L1 agents, suppresses VEGF expression and promotes vascular normalization.…”
Section: Synergic Effects Of Anti-vegf and Anti-pd-1/pd-l1 Monoclonal Antibodiesmentioning
confidence: 99%
“…VEGF is also known to suppress TILs via multiple mechanisms, including suppressing endothelial cell activation, inhibiting TNFα-mediated gene regulation, and blocking dendritic cell maturation thereby reducing T-cell activation ( 106 , 107 ). In preclinical models, VEGF inhibition synergized with PD-1 blockade and reduced T-cell exhaustion, and in clinical studies combinations of therapies including ICIs and TKIs have demonstrated improved TIL recruitment and improved PFS ( 108 ). The IMpower150 study, for example, demonstrated improved PFS of EGFR m NSCLC patients who had disease progression on or did not tolerate an EGFR TKI when they were treated with a combination of chemotherapy, ICI therapy, and VEGF-inhibition as described above ( 56 , 76 ).…”
Section: Discussionmentioning
confidence: 99%